Salvianolic Acid B Ameliorates Cognitive Deficits Through IGF-1/Akt Pathway in Rats with Vascular Dementia - Xiaowei Ma; Weiwei Xu; Zhongxia Zhang; Na Liu; Jie Yang; Mingwei Wang; Yanyong Wang (Cellular Physiology and Biochemistry, 2017)
BackgroundAims: Salvianolic acid B (SalB) is a natural polyphenolic compound enriched in Salvia miltiorrhiza Bunge. Our study was designed to explore the role of Sal B on cognitive impairment in vascular dementia (VD) model rats, as well as its possible molecular mechanisms. Methods: Rats were randomly divided into four groups (n = 15 for each group): Control group, Sal B group (normal Sprague Dawley rats treated with Sal B), VD group and VD + Sal B group. The VD group rats were established by permanent bilateral common carotid artery occlusion (BCCAO). Animals in the Control and Sal B group received the same operation without bilateral common carotid arteries occlusion. The animals in Sal B group and VD + Sal B group received Sal B (20 mg/kg) orally once a day for consecutive 6 weeks. We investigated the effects of SalB on BCCAO-induced cognitive deficits rats models via the Morris water maze experiment. To explore the mechanisms of Sal B on cognitive function, we detected the expression of IGF-1, Akt and p-Akt, and the rate of cell apoptosis in CA1 region. Results: Our results observed that hippocampal IGF-1 was decreased in VD model rats, while SalB reversed the alteration of IGF-1 levels. The expression of hippocampal Akt showed no significant difference between control and VD group, however, p-Akt level was significantly decreased in VD group. After 6 weeks of SalB treatment, p-Akt level was significantly increased. A large number of apoptotic neurons were found in VD model rats, while SalB prevented apoptosis of hippocampal neurons in CA1 region in VD model rats. Conclusion: SalB significantly ameliorated cognitive deficits in BCCAO-induced VD model rats. The potential mechanism underlying the protective effects may be mediated through IGF-1/Akt pathway.